PENGARUH TRANSPARANSI DAN AKUNTABILITAS TERHADAP KINERJA INSTANSI PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG BANDUNG - Marismiati, Marismiati; Hardiyanti, Marlita (Universitas Logistik dan Bisnis Internasional, 2025)
In government agencies, accountability and transparency are the main principles for achieving good corporate governance results. The aim of this research is to analyze the relationship between transparency and accountability and agency performance at KPKNL Bandung. This research adopted a quantitative approach by collecting data through questionnaires distributed to 44 participants. A two-tailed test is used to test the hypothesis. Data were analyzed using descriptive statistical analysis, validity test, reliability test, normality test, multiple correlation analysis, multiple linear regression analysis, coefficient of determination, T test, and F test. From the results of this research, the T test analysis shows that transparency or accountability has an effect on performance agencies and the F test show that transparency and accountability have a significant effect on company performance simultaneously with a coefficient of determination of 47.7%.